Improving the Quality of Human Upper Urinary Tract Specimens by Cryobiopsy - Klein, Jan T.; John, Axel; Bohnert, Lars; Enderle, Markus D.; Linzenbold, Walter; Bolenz, Christian (Frontiers in Oncology, 2022)
Objective: The quality of histopathological specimens obtained from the upper urinary tract with conventional flexible ureterorenoscopic biopsy needs to be improved. We investigated the feasibility and biopsy quality of specimens obtained by cryobiopsy, compared with standard ureterorenoscopic biopsy techniques in a human ex vivo model. Materials and Methods: Human ureters obtained from nephrectomy specimens (N=12) were dissected and canulated with an ureteral access sheath. Ureterorenoscopic biopsies were randomly obtained from different sites of the renal pelvic caliceal system using different types of instruments. The performance of two newly developed flexible cryoprobes with outer diameters of 1.1mm (CB11) and 0.9mm (CB09) was compared with that of the biopsy forceps(FB) and Bigopsy(BiG) and two different Dormia baskets N‐Gage(NG) and Zero‐Tip(ZT). We assessed the feasibility of the various biopsy techniques based on the number of biopsy attempts needed to obtain macroscopically discernible biopsies. The specimens were examined histopathologically for size, biopsy quality, presence of various artifact types, and representativeness. Results: Biopsies taken with the cryoprobes showed a higher biopsy quality than biopsies taken with the comparative instruments. The CB11 provided significantly larger biopsies than forceps biopsies and also than biopsies with ZT. The CB09 was able to collect larger samples when compared with the FB and BiG biopsy forceps. There were no significant differences in artifact area, except for the CB11 cryoprobe compared with the NG. To clarify the results a subdivision of larger or smaller than 20% artifact area was performed. A significant difference was found between CB11 and the forceps biopsies, as well as between CB11 and NG and ZT in favor of the cryoprobe. The representation of the histopathological sample was also determined. Biopsies taken with CB11 were more representative compared with forceps biopsies BiG and FB and basket biopsies NG and ZT. Conclusions: In a standardized comparative ex vivo setting, larger biopsies were obtained by using the cryobiopsy technique with the CB11 probe. Qualitatively, cryobiopsy specimens were overlaid by fewer artifacts and a higher biopsy quality was achieved in histopathologic examination compared with standard instrumentation. Further stepwise development will transfer the promising cryobiopsy technique into the clinical setting